The Efficiency and Risk in Chinese Banking Sector - Gao, Qianhe (2016)
Efficiency and risk are two principal themes in banking sector. The purpose of this paper is to analysis the relationship between risk and efficiency as well as the efficiency performance of Chinese commercial banks. Based on this purpose, we estimate 51 Chinese commercial banks’ efficiency performance during 2010 – 2015 with Stochastic Frontier Analysis method. Besides, under a one-step approach, we discuss risk control variables’ influence on the inefficiency effects. According to the empirical analysis, we find that risk-averse banks and banks with less operational risk are more efficient than other banks, and the scale of bank is positive related to bank’s efficiency performance. Besides, thank to domestic advantage, domestic banks, especially Large Commercial Banks are found to be more efficient than foreign banks. In addition, listed banks are significantly more efficient than unlisted banks, which confirms the “Selection Effect”.